(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: The problem of widespread resistant bacteria has become a major threat to reduce the effectiveness of antibiotics worldwide. Objective: The aim of this study was to identify the bacterial pathogens from bold culture and determine their antibiotic susceptibility pattern. Methodology: This cross-sectional study was conducted in the department of Microbiology at Monno Medical College, Manikganj, Bangladesh during the period from January 2019 to December 2019 for duration of one year. Blood was collected according to blood collection guidelines and inoculated into BacT/ALERT FA plus and BacT/ALERT PF plus aerobic blood culture bottles respectively. After collection these bottles were immediately incubated in BacT/ALERT 3D (manufactured by bioMerieoux, France) a fully automated blood culture system. Antimicrobial susceptibility test was done for all isolated bacteria by disc diffusion method. Results: A total number of 180 patients were recruited, among them 12 (7%) yielded growth of different bacteria. The most frequently isolated bacteria were Streptococcus Spp 5(42%) followed by Staphylococcus aureus and Escherichia coli which were 4(33%) and 3(25%) respectively. Escherichia Coli which showed highly sensitive to Imipenum, Amikacin, Linezolid, Gentamicin (N=3, 100%). Conclusion: There were a high percentage of bacteria isolated from blood culture and resistant to several antibiotics. For the selection of appropriate antibiotic therapy in bacterial infections the antibiotic susceptibility testing is mandatory. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):48-53